Thiazole derivative-modified upconversion nanoparticles for Hg2+ detection in living cells. Issue 1 (26th November 2015) - Gu, Bin; Zhou, Yi; Zhang, Xiao; Liu, Xiaowang; Zhang, Yuhai; Marks, Robert; Zhang, Hua; Liu, Xiaogang; Zhang, Qichun
Abstract : Thiazole-derivative-functionalized upconversion nanoparticles (UCNPs) can detect Hg 2+ in living cells and show excellent photo stability and high selectivity. Abstract : Mercury ion (Hg 2+ ) is an extremely toxic ion, which will accumulate in human bodies and cause severe nervous system damage. Therefore, the sensitive and efficient monitoring of Hg 2+ in human bodies is of great importance. Upconversion nanoparticle (UCNPs) based nano probes exhibit no autofluorescence, deep penetration depth and chemical stability in biological samples, as well as a large anti-stokes shift. In this study, we have developed thiazole-derivative-functionalized UCNPs, and employed an upconversion emission intensity ratio of 540 nm to 803 nm ( I 540 / I 803 ) as a ratiometric signal to detect Hg 2+ in living cells showing excellent photo stability and high selectivity. Our nano probe was characterized using transmission electron microscopy (TEM) and powder X-ray diffraction (PXRD). The low cytotoxicity of our probe was confirmed by an MTT assay and the UCL test in HeLa cells was carried out by confocal microscopy. Our results demonstrated that organic-dye-functionalized UCNPs should be a good strategy for detecting toxic metal ions when studying cellular biosystems.